Descriptive Analysis of the Use of Twitter by Cinemaximum Movie Theaters During the Covid-19 Global Pandemic - Özgü Yolcu (Connectist Istanbul University Journal of Communication Sciences)
This study looked into how movie theaters used social media during the pandemic, through the example of Cinemaximum movie theaters and Twitter. The reason for selecting Cinemaximum is that it is Turkey’s largest cinema chain and its movie theaters have the largest number of followers on social media. The study used the descriptive analysis and the content analysis method to examine 1006 tweets shared by Cinemaximum on Twitter between January 1 and December 15, 2020. At the end of the study it was seen that the Cinemaximum Twitter account was used actively in line with the company’s needs during the global pandemic. Differences were seen between shares posted prior to 16 March and those posted after this date. The topic codes identified in the Tweets were classified under 16 different categories. It was seen that the topics covered most in Tweets posted when movie theaters were open were “Films” (movie showtimes and information about the movie to be shown); when movie theaters were closed, “Entertainment” (competitions, games, questions, riddles, messages promoting participation (tagging your friend, etc.), humor, interesting information); and in July, when preparations were being made to reopen movie theaters, “Preparations for reopening the theaters.” When viewed in general, it can be said that the Tweets shared when movie theaters were open and in July when preparations to reopen them were underway were written primarily for marketing purposes, with a focus on advertising and promotion, and that those written when movie theaters were closed were focused on public relations.